The International Context of Indonesia's Omnibus Law: A bibliometric review - Mustaring Mustaring (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This research examines the perspectives of legal professionals on omnibus legislation in Indonesia, a legal and human rights issue. We have done data searches on hundreds of legal papers that address concerns relating to the law of copyright on the job. Using the keyword system on Google Search, several domestic and international legal periodicals are combed for data. He maintained his efforts to engage the coding system thoroughly with an in-depth examination and a high level of interpretation in order to understand how it may solve issues by emphasizing the quality and integrity of the data. On the basis of the research data and debate, the vast majority of legal professionals believe it to be a fantastic legal change. Nonetheless, the majority of them continue to dispute its efficacy and execution in light of the court's recent ruling that the Creative Economy and Work Law is unconstitutional with conditional enforcement. This conclusion will hopefully influence the legal review section in Indonesia